Nine years of monitoring ash dieback in the floodplain forest of Leipzig, Germany - Mathias Scholz; Rolf A Engelmann; Valentin Burghard; Ferndanda Chavez; Julie Fausser; Torben Frahm; Demian Genau; Stefanie Henkel; Christian Hecht; Franziska Löffler; Nico Spaarkogel; Jonas Till; et al. (PANGAEA, 2025)
As part of the Lebendige Luppe project, ash dieback disease was recorded on European ash trees (Fraxinus excelsior, trunks >5cm breast height diameter) on 60 plots (each 2500m^2) in the late summers of 2016 to 2024. The trees were assessed according to Langer et al. (2015). However, an additional category 6 (dead tree) was introduced to distinguish between dead and dying trees. The selection of trees (according to their size) was based on 2 forest inventories (2016 and 2020) (Rieland et al. 2024, Scholz et al. 2022). As a result, new trees were added for recording in 2021. From 2020, the additional parameter Tree damage class, ash bark beetle was introduced to assess the damage caused by the ash bark beetle in 4 categories. From 2023, an additional parameter Tree damage class, ash dieback crown was introduced, which based on Lenz et al. (2012) and indicates the damage in the crown of the tree. This classification was added because, unlike the Langer et al. (2015) classification, it describes the damage class independently of the beetle infestation. A comparison of the different damage classifications enables a better description of the damage pattern. A more detailed description of the three parameters used (Tree damage class, ash dieback; Tree damage class, ash bark beetle and Tree damage class, ash dieback crown) is provided in the dataset comment.